EVALUATION OF LIGHT STRAWBERRY AND GUAVA JELLIES STABILITY - MOURA, SÍLVIA CRISTINA SOBOTTKA ROLIM DE; PRATI, PATRÍCIA; VISSOTTO, FERNANDA ZARATINI; RAFACHO, MARINA DOS SANTOS (Revista Brasileira de Engenharia de Biossistemas, 2009)
The objective of this research was to evaluate the stability of light strawberry and guava jellies storedin 240 g flint glass pots. For such, two formulas (1-strawberry jelly and 1-guava jelly) were prepared inthe lab pilot plant (open pan with steam jacket) and measured the attributes such as pH, solublesolids, water activity, and syneresis. In order to evaluate the stability, the samples remained stored for180 days in controlled temperature chambers - 10°C (control) and 25°C (commercial sample) withlight absence. At every 30-day intervals, sensorial analyses of the following elements were performedduring 180 days: general aspect, color, fragrance, texture, and flavor. The most relevant results wereobtained from that samples stored at 25ºC which showed the highest quality reduction, mainly onaspect, color and flavor attributes. The estimated shelf-life for light strawberry and guava jellies sampleswas 5 to 7 months